LOB Domain Proteins: Beyond Lateral Organ Boundaries. (February 2016) - Xu, Changzheng; Luo, Feng; Hochholdinger, Frank
Abstract : LATERAL ORGAN BOUNDARIES DOMAIN (LBD) proteins defined by a conservedL ATERALO RGANB OUNDARIES (LOB) domain are key regulators of plant organ development. Recent studies have expanded their functional diversity beyond the definition of lateral organ boundaries to pollen development, plant regeneration, photomorphogenesis, pathogen response, and specific developmental functions in non-model plants, such as poplar and legumes. The identification of a range of upstream regulators, protein partners, and downstream targets of LBD family members has unraveled the molecular networks of LBD-dependent processes. Moreover, it has been demonstrated that LBD proteins have essential roles in integrating developmental changes in response to phytohormone signaling or environmental cues. As we discuss here, these novel discoveries of LBD functions and their molecular contexts promote a better understanding of this plant-specific transcription factor family. Trends: LBD genes encode a family of plant-specific transcription factors that are essential for lateral organ development in higher plants. Functional diversity of the LBD family exceeds lateral organ boundaries formation by defining pollen development, plant regeneration, photomorphogenesis, pathogen response, and some specific developmental processes in grass, wood, and fruit species. The LBD-dependent developmental programs depend on the cooperative action of the LBD-mediated molecular pathways, which comprise a range of newly identified upstream regulators, protein partners, and downstream targets of LBD family members. The integration of developmental changes induced by phytohormones or environmental stimuli requires the functions of LBD proteins.